1991
DOI: 10.1128/mcb.11.7.3454
|View full text |Cite
|
Sign up to set email alerts
|

Differential regional expression of three natriuretic peptide receptor genes within primate tissues.

Abstract: The natriuretic peptide receptors are three homologous cell surface proteins, each with a single transmembrane domain. The atrial natriuretic peptide receptor type A (ANPRA) and the homologous receptor type B (ANPRB) are both membrane guanylyl cyclases that synthesize cyclic GMP as an intracellular second messenger. The third receptor in this family, the atrial natriuretic peptide receptor type C (ANPRC), is not coupled to cyclic GMP production. We report on the distribution of the ANPRA, ANPRB, and ANPRC mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
90
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(100 citation statements)
references
References 42 publications
9
90
1
Order By: Relevance
“…In contrast, in the presence of NEP inhibition, CNP has a natriuretic action in dogs, which is due to inhibition of distal sodium reabsorption without increasing urinary cGMP excretion (50). The reason for our failure to observe an increase in the renal excretion of sodium after infusions of CNP into anesthetized normotensive or hypertensive rats in the present study may be the absence of ANP-B receptors in rat kidneys (39,40), as already mentioned.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In contrast, in the presence of NEP inhibition, CNP has a natriuretic action in dogs, which is due to inhibition of distal sodium reabsorption without increasing urinary cGMP excretion (50). The reason for our failure to observe an increase in the renal excretion of sodium after infusions of CNP into anesthetized normotensive or hypertensive rats in the present study may be the absence of ANP-B receptors in rat kidneys (39,40), as already mentioned.…”
Section: Discussioncontrasting
confidence: 52%
“…It has also been found that CNP has a much stronger effect than ANP in lowering blood pressure in anesthetized dogs, whereas ANP is more potent in increasing plasma cGMP and the urinary excretion of sodium and cGMP (46). The reason why CNP did not decrease the blood pressure in hypertensive or normotensive anesthetized rats in this study is so far unclear, but a possible explanation could be the absence of ANP-B receptors in rat kidney (39,40) as mentioned above.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…The ANF-R~A subtype is mostly specific for both ANF and brain natriuretic peptide (BNP) [3,4] and is found at high concentration in many target organs of these natriuretic peptides [5]. The ANF-R~c subtype is mainly specific for C-type natriuretic peptide (CNP) [2] and its distribution is limited to tissues of neuronal origin [5]. The ANF-Rm subtype, which has not yet been cloned, displays higher affinity for ANF than for BNP [1] and does not recognize CNP.…”
Section: Introductionmentioning
confidence: 99%
“…The ANF-Rm subtype, which has not yet been cloned, displays higher affinity for ANF than for BNP [1] and does not recognize CNP. The ANF-Rz receptor class, which has been cloned, does not discriminate between these peptides [6], is widely distributed [5] and recognizes biologically inactive ANF derivatives e.g. [CysZt~]rANF-(102-116)x-NH2 (C-ANF).…”
Section: Introductionmentioning
confidence: 99%